The Immune and Non-Immune Pathways That Drive Chronic Gastrointestinal Helminth Burdens in the Wild - Babayan, Simon A.; Liu, Wei; Hamilton, Graham; Kilbride, Elizabeth; Rynkiewicz, Evelyn C.; Clerc, Melanie; Pedersen, Amy B. (Frontiers in Immunology, 2018)
Parasitic helminths are extremely resilient in their ability to maintain chronic infection burdens despite (or maybe because of) their hosts’ immune response. Explaining how parasites maintain these lifelong infections, identifying the protective immune mechanisms that regulate helminth infection burdens, and designing prophylactics and therapeutics that combat helminth infection, while preserving host health requires a far better understanding of how the immune system functions in natural habitats than we have at present. It is therefore necessary to complement mechanistic laboratory-based studies with studies on wild populations and their natural parasite communities. Unfortunately, the relative paucity of immunological tools for non-model species has held these types of studies back. Thankfully, recent progress in high-throughput ‘omics platforms provide powerful and increasingly practical means for immunologists to move beyond traditional lab-based model organisms. Yet, assigning both metabolic and immune function to genes, transcripts, and proteins in novel species and assessing how they interact with other physiological and environmental factors requires identifying quantitative relationships between their expression and infection. Here, we used supervised machine learning to identify gene networks robustly associated with burdens of the gastrointestinal nematode Heligmosomoides polygyrus in its natural host, the wild wood mice Apodemus sylvaticus. Among the among 17,639 transcripts we detected in thirty-four mice spanning two wild populations over two different seasons, gene networks that robustly predicted H. polygyrus burdens included well-known effector and regulatory immune genes, but also revealed a number of genes associated with the maintenance of tissue homeostasis and haematopoiesis that have so far received little attention. We then tested the effect of experimentally reducing helminth burdens through drug treatment on those putatively protective immune factors. Despite the near elimination of H. polygyrus worms, the treatment had surprisingly little effect on gene expression. Taken together, these results suggest that hosts balance tissue homeostasis and protective immunity, resulting in relatively stable immune, and consequently, parasitological profiles. In the future, applying our approach to larger numbers of samples from additional populations will help further increase our ability to detect the immune pathways that determine chronic gastrointestinal helminth burdens in the wild.